Cytoskeleton Structure and Study of Its Role in the Cell - Hamdard, Mohammad Hamid (Journal of Natural Sciences – Kabul University, 2020)
The cytoskeleton is a complex network of protein fibers in eukaryotic cells that extends throughout the cell's cytoplasm, from one side of the cell membrane to the other. The main functions of the cytoskeleton are to maintain the cell's shape, provide support, transport vesicles inside the cell, assist in cell division, facilitate organelle migration, and enable intracellular movement. The cytoskeleton is composed of three types of protein filaments: microtubules, microfilaments, and intermediate filaments. These filaments are distinguished by their size, with microtubules being the thickest and microfilaments the thinnest. Microfilaments and microtubules are made from small subunit proteins capable of fast contraction. Cytoskeleton composed from three types of protein filaments; microtubules, microfilaments, and intermediate filaments these filaments are distinguished by their size and proteins with microtubules being the thickest and microfilaments being the thinnest fiber in cytoskeleton. Microfilament and microtubule are made from small subunit proteins which are capable for fast contraction.